Numerical and Experimental Investigations of the Effect of PVD and Vacuum Pressure on the Degree of Saturation (Journal of Engineering, 2016)
Soft clays are generally characterized by low shear strength, low permeability and high compressibility. An effective method to accelerate consolidation of such soils is to use vertical drains along with vacuum preloading to encourage radial flow of water.  In this research numerical modeling of prefabricated vertical drains with vacuum pressure was done to investigate the effect of using vertical drains together with vacuum pressure on the degree of saturation of fully and saturated-unsaturated soft soils.  Laboratory experiments were conducted by using a specially-designed large consolidometer cell where a central drain was installed and vacuum pressure was applied. All tests were conducted with a vacuum pressure of 40 kPa applied for a period of 30 days where a degree of soil consolidation of 90% was attained.  At the end of the test period fifteen samples were taken from different locations distributed along the depth and radially to measure the water content. Consolidation settlements were recorded with time for all tests. The results showed that using vacuum pressure with vertical drains is a very effective method to accelerate consolidation of soils. As the thickness of unsaturated top layer increases, the settlement of soil surface decreases. The water content decreased after 30 days of application of the vacuum pressure.